Long-chain saturated fatty acids and its interaction with insulin resistance and the risk of nonalcoholic fatty liver disease in type 2 diabetes in Chinese - Jiang, Li-Peng; Sun, Hong-Zhi (Frontiers in Endocrinology, 2022)
ABSTRACT Objectives: This study aimed to explore relationships between long-chain saturated fatty acids (LSFAs) and nonalcoholic fatty liver disease (NAFLD) in patients with type 2 diabetes (T2D); and whether insulin action had an interactive effect with LSFAs on NAFLD progression. Methods: From April 2018 to April 2019, we extracted the electronic medical records of 481 patients with T2D who meet the inclusion and exclusion criteria from the Second Affiliated Hospital of Dalian Medical University. Ultrasound was used to estimate NAFLD at admission. Logistic regression analysis were used to estimate odds ratios (OR) and 95% confidence intervals (CI). The additive interaction was carried out to estimate interactions between LSFAs and insulin resistance (IR) in NAFLD patients with T2D. Results: Myristic acid (14:0) and palmitic acid (16:0) were positively associated with the risk of NAFLD (OR for myristic acid (14:0): 7.516, 3.557-15.882 and OR for palmitic acid (16:0): 4.071, 1.987-8.343, respectively). After adjustment for traditional risk factors, these associations were slightly attenuated but still highly significant. Co-presence of myristic acid (14:0)>72.83 μmol/L and IR>4.89 greatly increased OR of NAFLD to 9.691 (4.113-22.833). Similarly, co-presence of palmitic acid (16:0)>3745.43μmol/L and IR>4.89 greatly increased OR of NAFLD to 6.518(2.860-14.854). However, stearic acid (18:0) and risk of NAFLD have no association. Moreover, there was no association between very-long-chain SFAs (VLSFAs) and risk of NAFLD. Conclusions: Myristic acid (14:0) and palmitic acid (16:0) were positively associated with the risk of NAFLD in T2D patients in China. High IR amplified the effect of high myristic acid (14:0) and high palmitic acid (16:0) on NAFLD. Keywords: myristic acid (14:0), palmitic acid (16:0), IR, NAFLD, T2D